2022
DOI: 10.1155/2022/9280269
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Health Insurance Utilization and Its Associated Factors among Rural Households in Akaki District, Oromia, Ethiopia, 2021

Abstract: Background. Community-based health insurance is widely recognized as the most effective way to achieve universal health coverage (UHC) with adequate financial protection against healthcare costs, to promote equal access to high-quality healthcare, increase financial security, and enhance social cohesion and solidarity. Objective. The objective of this study was to determine community-based health insurance utilization and its associated factors among rural households in Akaki District, Oromia special zone surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…This finding is consistent with those from other settings elsewhere [ 29 31 ], which shows the richest households were more likely to use the CBHI program when compared the poorest households. In addition, it is in line with the previous studies [ 26 , 28 , 32 , 33 ], which show income significantly positively affected CBHI enrollment. This study was not in line with the previous studies [ 34 ], poor wealth status households were more likely willing to pay/enroll for CBHI than rich household heads.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with those from other settings elsewhere [ 29 31 ], which shows the richest households were more likely to use the CBHI program when compared the poorest households. In addition, it is in line with the previous studies [ 26 , 28 , 32 , 33 ], which show income significantly positively affected CBHI enrollment. This study was not in line with the previous studies [ 34 ], poor wealth status households were more likely willing to pay/enroll for CBHI than rich household heads.…”
Section: Discussionsupporting
confidence: 92%
“…This study also revealed that households with 4 up to 6 members were more likely to enroll in the CBHI scheme than households with 1 up to 3. This study was consistent with the previous studies [ 28 , 38 ], which show family size had a significant positive effect on dropout of households from the CBHI scheme This study contradicts the previous study [ 26 , 32 , 39 ], which shows family size had a significant negative effect on CBHI enrollment. Moreover, this study was not in line with the study [ 31 ], which shows the number of family sizes in the household had no significant effect on CBHI enrollment.…”
Section: Discussionsupporting
confidence: 89%
“…The studies were conducted from 2017 to 2022. Regarding the distribution of the studies across the region, five were from Amhara [ 40 , 41 , 43 , 45 , 47 ], four from Oromia [ 34 , 35 , 44 , 46 ], two from Sidama [ 39 , 42 ], one from Somali [ 37 ], one from Southern Nations, Nationalities, and Peoples’ Region (SNNPR) [ 36 ], and two from Addis Ababa [ 38 , 48 ]. In all of the studies, data was collected by a face-to-face interview using a pretested, interviewer-administered questionnaire ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (11 cross-sectional and 4 case-control) with a total of 8418 study participants were considered [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Both the minimum (n = 262) [41] and the maximum(n = 1014) [43] sample size were from the Amhara region.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Although equity to health service is the underlying principle of major global public health strategies such as the health sector reforms spearheaded by the World Bank and the current Sustainable Development Goals (SDGs) 3, its implementation is a significant public health challenge [3,5]. Many studies revealed that several low-income countries are challenged to sustain healthcare financing [6,7]. However, achieving universal health coverage, including financial risk protection, access to quality healthcare services, and access to safe, adequate, quality, and affordable essential medicines are fundamental for sustaining growth and development [8].…”
Section: Introductionmentioning
confidence: 99%